An Ontological Security Analysis of Americanism in Turkish Foreign Policy, 1945-1960 - Emine Alp (Siyasal: Journal of Political Sciences)
This article aims to draw attention to an aspect of Turkish foreign policy that has not been sufficiently theorized, especially within the framework of Ontological Security Theory. It attempts to show that one of the motives of Turkish foreign policy for its increasing orientation towards the West in the early Cold War period was to complete the three-centurylong project of Westernization and to find a relevant place in the international system. As an alternative version to the European model of Westernism or modernization, Americanism in Turkish foreign policy appeared as an illustration of the ontological security concerns of the country alongside its political, economic, and security interests. Under the Western security umbrella, the Turkish state sought not only to protect its territory from the Soviet threat but also to secure its state identity as an important part of Western civilization. Accordingly, Türkiye adopted an anti-Soviet stance and tried to secure its place in the Western bloc, but often acted in favor of the United States and against its own national interests. This attitude has implications for the Ontological Security approach, which interprets the irrational and identity-oriented behavior of the nation-states as an effort to maintain the security of their ‘being.’ Consequently, this study argues that the pursuit of ontological security was an important element of Turkish foreign policy during this period.